Social Capital Shapes Young People's Business Opportunities in Batam City - Maria Susanti; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
The City of Batam has great potential that can be utilized in various fields, particularly the economy. This potential is also one of the advantages that young people can utilize to build their businesses through social capital. The strength of this social capital lies in the relationships and closeness of the social network young people have. This social capital is built to create creativity and motivation for solidarity through entrepreneurial activities. Using qualitative research methods and descriptive approaches, researchers found 6 informants, including business owners who helped young people build their social capital, students, and workers who had implemented business opportunities. The results of this research aim to help young people better utilize their free time by being creative and innovative based on their talents. When something has a good and profitable impact, there will undoubtedly be a lot of interest in pursuing it.